Ballistic impact response of an UHMWPE fiber reinforced laminate encasing of an aluminum-alumina hybrid panel. (December 2015) - O'Masta, M.R.; Compton, B.G.; Gamble, E.A.; Zok, F.W.; Deshpande, V.S.; Wadley, H.N.G.
Abstract: The impact response of an ultrahigh molecular weight polyethylene (UHMWPE) fiber reinforced polymer matrix composite laminate has been investigated. The laminate encapsulated an aluminum alloy sandwich panel whose corrugated core was filled with prismatic alumina inserts. The laminate encased hybrid core target could sustain ceramic prism base impacts by a spherical, 12.7 mm diameter steel projectile with velocities in excess of 2.7 km s −1 . This was 150% higher than the ballistic limit of an equal areal density, similarly encapsulated aluminum plate target. By contrast, when the projectile impacted a hybrid core target at the apex of a ceramic prism insert, failure of the UHMWPE laminate on the rear face occurred at a lower impact velocity. High-speed imaging, three-dimensional digital image correlation and x-ray tomography measurements are used to show that upon impact the projectile and the ceramic insert fragment. These fragments then load the UHMWPE laminate on the rear face with a significantly reduced pressure compared to the impact pressure of the projectile on the front surface of the target. The loading area on the inner surface of the rear laminate was highest for a prism base impact and lowest for a prism apex impact. The inability to penetrate the rear laminate of the base impacted samples is consistent with the recent identification of an impact pressure controlled mechanism of progressive penetration in this class of laminate. Highlights: An UHWMPE encased Al/Al2 O3 panel had a higher impact resistance than similar weight targets. The Al/Al2 O3 panel fragmented the projectile and redistributed its momentum. Prior to arrival of debris, the deforming Al/Al2 O3 panel pre-accelerated the laminate. Distributing the impact momentum and setting the laminate in motion combine to suppress local laminate failure.